Highly Productive Tropical Seagrass Beds Support Diverse Consumers and a Large Organic Carbon Pool in the Sediments - Lee, Chen-Lu; Lin, Wei-Jen; Liu, Pi-Jen; Shao, Kwang-Tsao; Lin, Hsing-Juh (Diversity (Basel), 2021)
Tropical seagrass beds are productive coastal ecosystems that are important blue carbon sinks and crucial habitats and feeding grounds for consumers at high trophic levels. To understand how energy sustains the ecosystem from seagrass production, we constructed an Ecopath trophic model to reveal the possible pathways of energy flow in the tropical seagrass beds around Dongsha Island, South China Sea. The model indicates that Dongsha seagrass beds were developing but well-structured ecosystems. The productive seagrasses were rarely directly consumed by herbivores and, ultimately, flowed into detrital pools. Detritus was the main food source used to support diverse consumers in the food web. Nevertheless, the low cycling rate (2.74%) suggests that most detritus was not reused or exported and was stored as a large organic carbon pool in the sediments. The detritus-feeding invertebrates are keystone groups in the Dongsha seagrass beds, as they recycle energy from detritus and transfer to top predators such as sharks. The predation of top predators affected the biomasses of other compartments, leading to strong top-down control via a trophic cascade effect.